Factor Affecting Incident Diarrhea In Slum Areas Disposal Rubbish - Anurogo, Dito; Yanik, Carri Noer Fida; Auliah, Rezki; Yermi, Yermi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Background : Diarrhea​ Still become problem health mainstay in Indonesia, especially in the regions with sanitation bad and condition environment that is not healthy. Slum areas around place disposal rubbish own risk tall to disease this because limitations access to clean water, cleanliness food, as well as behavior life clean and healthy low. Research purposes this aiming for know factors that influence incident diarrhea in the area adjacent slums​ with place disposal rubbish. Research methods use design descriptive analytic with cross-sectional approach. The sample consists of from 250 heads family living nearby​​ place disposal waste in City X, selected through purposive sampling technique. Data collected through questionnaire, observation field, and interviews in depth. Data analysis was carried out using chi-square and regression tests logistics multivariate. Results: Factors that significantly significant influential to incident diarrhea is clean water quality (p=0.002), habits wash hand (p=0.001), management waste domestic (p=0.003), and density occupancy (p=0.008). Conclusion: Necessary intervention cross sector for increase clean water access, education health public about sanitation basics, and improvements environment settlements.